Antimicrobial susceptibility of Acinetobacter clinical isolates and emerging antibiogram trends for nosocomial infection management - Muhammad Sohail; Abid Rashid; Bilal Aslam; Muhammad Waseem; Muhammad Shahid; Muhammad Akram; Mohsin Khurshid; Muhammad Hidayat Rasool (Revista da Sociedade Brasileira de Medicina Tropical, 2016)
Abstract: Introduction: The drug resistant Acinetobacter strains are important causes of nosocomial infections that are difficult to control and treat. This study aimed to determine the antimicrobial susceptibility patterns of Acinetobacter strains isolated from different clinical specimens obtained from patients belonging to different age groups. METHODS: In total, 716 non-duplicate Acinetobacter isolates were collected from the infected patients admitted to tertiary-care hospitals at Lahore, Pakistan, over a period of 28 months. The Acinetobacter isolates were identified using API 20E, and antimicrobial susceptibility testing was performed and interpreted according to Clinical and Laboratory Standards Institute (CLSI) guidelines. RESULTS: The isolation rate of Acinetobacter was high from the respiratory specimens, followed by wound samples. Antibiotic susceptibility analyses of the isolates revealed that the resistance to cefotaxime and ceftazidime was the most common, in 710 (99.2%) specimens each, followed by the resistance to gentamicin in 670 (93.6%) isolates, and to imipenem in 651 (90.9%) isolates. However, almost all isolates were susceptible to tigecycline, colistin, and polymyxin B. CONCLUSIONS: The present study showed the alarming trends of resistance of Acinetobacter strains isolated from clinical specimens to the various classes of antimicrobials. The improvement of microbiological techniques for earlier and more accurate identification of bacteria is necessary for the selection of appropriate treatments.